Реакція західного світу на злуку західноукраїнської уніатської церкви з російською православною в 1946 році - Концур-Карабінович, Наталія; Kontsur-Karabinovych, Natalija (My University, 2015)
У науковій статті показано штучність розриву Берестейської унії й процесу «возз’єднання» з РПЦ, репресивні механізми впливу держави на ієрархів, священиків і віруючих УГКЦ, жертовну готовність греко-католицького духовенства відстоювати свою віру всупереч офіційній політиці радянської влади очима світового суспільства. Простежено відголос цих подій у західному світі.The process of abolishment of the church had different forms but its efficiency generally depended on the level of repressive violent acts of soviet special organs. For the generalization of punitive actions the authority used open forged and ideological accusation of the church of the cooperation with the Nazi, provocations and blackmail towards the Greek-Catholic priests and monks. Arrests of the higher authority of UGCC in spring 1945 demonstrated cynicism of the soviet regime concerning civil rights of the Greek-Catholic clergy and readiness to achieve the necessary result at any cost. The declared abolishment of the Brest Union and «directing» of Greek-Catholic people to orthodox belief with the help of manipulation of the initiative group was fully controlled and worked out by the organs of the National Committee of State Security and accompanied by constant administrative and repressive pressure on the clergy and the faithful.
Reaction of the Western World on Connection of Zakhidnoukrainskoy Uniatskoy Church with Russian Orthodox in 1946 Year
Keywords: антиунійна політика; греко-католики; Львівський собор; antiunion policy; the greek-catholic faithful; the Lviv Union; Ukrainian greek-catholic church; vozzednannya; world reaction